Contextual Learning Module Based on Multiple Representations: The Influence on Students’ Concept Understanding - Uslima, Ummul; Ertikanto, Chandra; Rosidin, Undang (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to describe the effect of using contextual learning module based on multiple representations of static fluid material toward students' conceptual understanding. The sample of this research was the students of class XI IPA 2 and XI IPA 3 in SMA N 1 Trimurjo, Central Lampung. This research was conducted using Pretest-Posttest Control Group Design. Data were tested with N-gain analysis, normality test, homogeneity test and Independent Sample T-test. Results from the Independent Sample T-test value of the Sig value. (2-Tailed) was less than 0.05 which is 0.036, then it can be stated that there is a significant influence of contextual learning module based on multiple representations toward the students’ conceptual understanding. Based on the N-gain value, the average N-gain concept comprehension in the experimental class was 0.56 (medium category), while the control class was 0.46 (medium category). Contextual learning modules based on multiple representations can improve students’ conceptual understanding.